Core-shell type-II spherical quantum dot under externally applied electric field - Holovatsky, Volodymyr; Chubrei, Maryna; Duque, Carlos (Elsevier, 2022)
This study presents a simple one-band model within the effective mass approximation to describe the electric field impact on the energy structure and interband electron quantum transitions in type-II CdSe/ZnTe and ZnTe/ CdSe spherical quantum dots. The dependencies of the oscillation strength and the light absorption coefficient on the externally applied electric field are calculated by the diagonalization method for spherical quantum dots of different sizes. It is shown that in the absence of an electric field and due to the spherical symmetry of nano- system, only quantum transitions with Δl = 0 (1se − 1sh, 1pe − 1ph, 1de − 1dh, 1se − 2sh,...) are allowed. The oscillator strength of quantum transitions between electron and hole excited states is greater than between the ground states. The electric field breaks the spherical symmetry, therefore, the oscillator strength of the 1se − 1ph, 1se − 1ph, 1se − 1dh,... quantum transitions, which are forbidden for spherical symmetric systems, increase when electric field strength grows. Under electric field effects, the oscillator strength of allowed Δl = 0 quantum transitions decreases. Finally, we observed that the absorption peaks in the quantum dot spectra under electric field influence are shifted to the low-energy region.
Keywords: Type-II quantum dots Oscillator strength Exciton energy Interband transition Electric field Diagonalization method